The Influence of Work Motivation and Competence on Employee Performance Through Employee Engagement - Ramadhan, Dany Fauzan; Prasetya, Arik; Hutahayan, Benny (FIA UB, 2025)
Human resources are a valuable asset for an organization. Hence, it must be maintained, and various possibilities that could impact achieving the organization's goals should be avoided. Performance is a crucial factor in achieving organizational goals as it positively impacts customer satisfaction, making it a determining factor for long-term success for the organization. In 2020 and 2023, the performance of employees at PT Indo Kordsa experienced a decline. This study examines the factors that can influence employee performance and analyzes the differences between permanent and contract employees' performance at PT Indo Kordsa. This research uses a quantitative method by distributing an online survey through a Google Form to 348 respondents. The data analysis employs SPSS tools and the Sobel test. The results of this study indicate that work motivation and competence significantly affect employee engagement. Furthermore, work motivation, competence, and employee engagement significantly affect employee performance. Additionally, Employee engagement variables have been shown to mediate the relationship between work motivation and competence with employee performance, and the analysis results show a significant influence of work motivation and competence on employee performance through employee engagement. However, there is no difference between permanent and contract employee performance.